2020
DOI: 10.1038/s41598-020-67952-0
|View full text |Cite
|
Sign up to set email alerts
|

Generalizable deep temporal models for predicting episodes of sudden hypotension in critically ill patients: a personalized approach

Abstract: the vast quantities of data generated and collected in the intensive care Unit (icU) have given rise to large retrospective datasets that are frequently used for observational studies. the temporal nature and fine granularity of much of the data collected in the ICU enable the pursuit of predictive modeling. in particular, forecasting acute hypotensive episodes (AHe) in intensive care patients has been of interest to researchers in critical care medicine. Given an advance warning of an AHe, care providers may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
2
13
0
1
Order By: Relevance
“…Similar monitoring of telemetry changes has shown that machine learning and AI techniques can be applied to telemetry waveforms to also predict sepsis (Bravi et al, 2012 ). Preliminary studies have also applied AI models to predict hypotension (Chan et al, 2020 ). Sequential monitoring of variables used in a risk score may provide better mortality prediction than a single snapshot assessment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Similar monitoring of telemetry changes has shown that machine learning and AI techniques can be applied to telemetry waveforms to also predict sepsis (Bravi et al, 2012 ). Preliminary studies have also applied AI models to predict hypotension (Chan et al, 2020 ). Sequential monitoring of variables used in a risk score may provide better mortality prediction than a single snapshot assessment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Больные с идентифицированным гипервоспалительным либо гиповоспалительным фенотипом имеют существенно различающиеся клинические исходы и дифферен-цированный ответ на ИВЛ, инфузионную терапию и симвастатин [41]. Гипервоспалительный субфенотип ассоциирован с шоковым состоянием, метаболическим ацидозом и худшим клиническим исходом [42][43][44].…”
Section: внедрение принципов пм в медицину критических состоянийunclassified
“…Patients who are admitted to ICU are very sick and therefore they tend to have a higher mortality rate than the average patients on the wards. With the development of artificial intelligence, many researchers have applied machine learning methods to study severe illnesses, such as sepsis [2][3][4][5][6][7], Acute kidney injury (AKI) [8][9][10][11], hypotension [12][13][14], etc. Early prediction of patients at high risk of deterioration within a short period of time would trigger immediate attention and intervention and thus would reduce the mortality rate at ICU, especially in low-and middle-income countries with limited health care resources [15][16][17].…”
Section: Introductionmentioning
confidence: 99%